Analysis of Compliance Factors of Chronic Kidney Failure Patients Undergoing Hemodialysis - Suhastinah, Suhastinah; Arifin, Syamsul; Suhartono, Eko; Panghiyangani, Roselina; Adhani, Rosihan (Journal La Medihealtico, 2024)
The aim is to determine the factors associated with compliance of chronic renal failure patients undergoing hemodialysis in RSUD Brigjend. H. Hasan Basry Kandangan Hospital. This type of research is analytic observational with a cross-sectional survey approach. The results of the bivariate analysis showed that there is a correlation between motivation and compliance in chronic renal failure patients undergoing hemodialysis with a Pvalue (0.000) < 0.05 and an OR of 22.222, a correlation between satisfaction and compliance in chronic renal failure patients undergoing hemodialysis with a Pvalue (0.000) < 0.05 and an OR value of 16.667, and a correlation between therapeutic communication and compliance in chronic renal failure patients undergoing hemodialysis with a Pvalue (0.004) < 0.05 and an OR value of 9.118. Based on the results of this study, it can be concluded that there is a correlation between motivation, satisfaction and therapeutic communication with compliance with undergoing hemodialysis in RSUD Brigjend. H. Hasan Basry Kandangan Hospital.